Immigration and public opinion in Europe: the case of the 2004 enlargement - Jeannet, A (2014)
After the enlargement of the European Union in 2004, large numbers of Central and Eastern Europeans moved to work in Western Europe. The aim of this thesis is to use the case of migration after the enlargement to further our understanding of the relationship between immigrant group size and natives’ attitudes. Recent scholarly debates raise questions about how immigration affects European societies and the political durability of European welfare states. This research puts forward two questions: Does an increase in Eastern European immigration after the enlargement explain differences in civic attitudes in Western Europe? And second, does this relationship (if any) depend on national contextual factors? The relationship between immigration and three categories of public attitudes are examined: attitudes towards immigration, attitudes towards welfare and attitudes of trust. This thesis draws on ethnic competition theory, which postulates that group competition over resources provokes the natives to perceive immigration as a threat to their own or their group’s interests. To test this theory, this study uses data from the European Social Survey from 2002 to 2010 to build multi-level pooled time series models. The results find only partial support for ethnic competition theory. When a greater proportion of E-8 migrants live in the country, individuals tend to have more positive views about immigration. The results also show that this positive relationship is weakened when national economic conditions are more precarious. Additionally, the results do not find that E8 migration is negatively related to Western European attitudes regarding trust or welfare. This implies that as more immigrants arrive, Europeans can potentially acknowledge immigration’s economic and cultural benefits. Moreover, these results challenge pessimistic scholarly predictions that immigration erodes trust and support for welfare in Europe. This thesis offers two academic contributions. First, it considers the case of E8 migration, which has been ignored by existing comparative attitudinal studies about immigration. Second, focusing on post-enlargement migration helps this thesis to overcome common empirical obstacles such as cross-country differences in immigrant composition and admission criteria.